Peristaltic Flow of the Bingham Plastic Fluid in a Curved Channel - Adnan, Farah Alaa; Abdul Hadi, Ahmad M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper, we study the peristaltic transport of incompressible Bingham plastic fluid in a curved channel. The formulation of the problem is presented through, the regular perturbation technique for small values of  is used to find the final expression of stream function. The numerical solution of pressure rise per wave length is obtained through numerical integration because its analytical solution is impossible. Also the trapping phenomenon is analyzed. The effect of the variation of the physical parameters of the problem are discussed and illustrated graphically.